Extraction of crude palm oil using supercritical CO2 - Masturah Markom; Harcharan Singh; Masitah Hasan (2002)
The effects of changing the operating pressure and temperature on the solvating strength of supercritical carbon dioxide and the solubility of crude palm oil in the solvent were discussed. The operating temperatures and pressures investigated are 40, 50 and 60°C, and 110, 140 and 200 bars. Changes in pressure showed a stronger influence on palm oil solubility in CO2 compared to temperature. The rate of extraction and the solubility of palm oil increased when the system pressure was increased (at constant temperature) or when the system temperature was decreased (at constant pressure). These results are comparable with the reported results of solubility of other vegetable oils such as soybean and olive oils. The change in the physical behaviour and the colour of the oil extracts and residues were also observed. It was discovered that the initial fractions of palm oil extracted were solid like while the latter fractions were semi-liquid. As the extraction progressed, the orange colour of the fractions became progressively more intense at 200 bars. At lower pressures of 140 and 110 bars, however the colour intensity was reduced, indicating decreasing density and solvating strength of the supercritical CO2